Uric Acid Concentration With Risk Factors For Hypertensionwith Coronary Heart Disease Patients Who Do Moderaty Intensity Physical Exercise - Amalia, Nindya; Dewi, Sianty; Sarvasti, Dyana (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Complication of hypertension causes 45% of deaths from heart disease. Programs for improving quality of life in heart disease patients such as Cardiovascular Prevention and Rehabilitation program, usually includes one component, which is to do moderate-intensity physical exercise. previous study suggested that moderate-to-high intensity physical exercise could increase uric acid. Aim: To examine the correlation between uric acid concentration and risk factors for hypertension in patients with coronary heart disease who do moderate intensity physical exercise. Method: This was a retrospective study using data from medical records with cross-sectional design. The sampling method used purposive sampling based on subjective consideration and the availability of certain criteria. Analysis used chi-square analysis Results: The data were taken from medical records from 2012 until July 2019. Sampling, which appropriates for inclusion and exclusion criteria in Husada Utama Hospital, was 30 samples, 25 male, and 5 female. The majority of subjects in this research was 56-65 years old. The youngest was 40 years old while the oldest was 77 years old. Data analysis results showed that patients who had hypertension risk factors and increased uric acid were 17 patients (85%) and who did not have hypertension risk factors1. They did not experience an increase were seven people (70%) from the chi-square test. significant with p = 0.003 (p